2016
DOI: 10.31234/osf.io/jkc4n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Empathy is hard work: People choose to avoid empathy because of its cognitive costs

Abstract: Empathy is considered a virtue, yet fails in many situations, leading to a basic question: when given a choice, do people avoid empathy? And if so, why? Whereas past work has focused on material and emotional costs of empathy, here we examined whether people experience empathy as cognitively taxing and costly, leading them to avoid it. We developed the Empathy Selection Task, which uses free choices to assess desire to empathize. Participants make a series of binary choices, selecting situations that lead them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…In addition to aversive feelings of distress and insecurity, recent research has explored why people experience aversion to suffering, particularly when confronted with the suffering of people on a mass scale (Cameron & Payne, 2011) or on encountering stigmatized others (Cameron, Harris, & Payne, 2016). People appear to make a motivated choice to avoid empathy for others’ suffering when they anticipate empathy to be too costly and effortful (Cameron et al, 2019; Cameron & Payne, 2011). People strategically avoid empathy and compassion just when more are needed.…”
Section: Barriers To Compassion Without the Relational Starting Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to aversive feelings of distress and insecurity, recent research has explored why people experience aversion to suffering, particularly when confronted with the suffering of people on a mass scale (Cameron & Payne, 2011) or on encountering stigmatized others (Cameron, Harris, & Payne, 2016). People appear to make a motivated choice to avoid empathy for others’ suffering when they anticipate empathy to be too costly and effortful (Cameron et al, 2019; Cameron & Payne, 2011). People strategically avoid empathy and compassion just when more are needed.…”
Section: Barriers To Compassion Without the Relational Starting Pointmentioning
confidence: 99%
“…In addition to concerns about emotional exhaustion and effort, when people think that they lack the efficacy to address other’s needs, they choose to avoid empathic engagement (Cameron et al, 2019). In contrast, increased confidence in one’s empathic abilities enhances empathic engagement (Cameron et al, 2019; Lim & DeSteno, 2019; Sharma & Morwitz, 2016). Likewise, the belief that empathy is a skill that can grow through one’s efforts increases people’s willingness to empathize when it is challenging (e.g., toward a member of an out-group; Schumann, Zaki, & Dweck, 2014).…”
Section: Barriers To Compassion Without the Relational Starting Pointmentioning
confidence: 99%
“…To more fully understand how principles of goal pursuit apply to empathic choices, future work should provide people with opportunities to select into empathyeliciting situations (i.e., situation selection; Gross, 2015) as a measure of motivation to empathize (for initial approach, see Cameron et al, 2017). Situation selection is relevant for empathic decisions-for example, early work on motivated empathy found that people avoided situations entailing high empathy when they anticipated high helping costs resulting from empathy (Shaw et al, 1994; see also Pancer et al, 1979).…”
Section: Refining Measurement Of Empathy Choicementioning
confidence: 99%
“…Others question whether the counselor's own emotions are actually helpful in the context of the therapeutic relationship. For example, vicarious experiences of emotions may be overwhelming to a counselor, and overidentification with the client's feelings could sideline the true focus of the counseling session (Bayne & Hays, 2017; P. Bloom, 2017; Cameron et al, 2019; Chikovani et al, 2015; Clark, 2010). It could also be argued that involvement of the counselor's emotional identification is more of a self‐focus than an other‐focus that filters the client's reality through the counselor's limited perspective (Clark, 2010; Coplan, 2011).…”
Section: Constructing Empathymentioning
confidence: 99%
“…Our goal with this question was to explore the counselors' own judgment of what made for effective counseling, as well as to acknowledge that counselors may value empathy at face value but still endorse less empathic responses when considering the client in context. Although empathy tends to be a widely accepted construct in counseling, some have critiqued whether it is always beneficial, with some arguing that empathy can be overly taxing and can contribute to an overfocus on negative emotional states (P. Bloom, 2017; Cameron et al, 2019; Chikovani et al, 2015). Hansen et al (2014) asserted that degree of accuracy is less important to humanistic counseling practice than degree of impact, suggesting that viewing a client in context could lead counselors to choose from a variety of responses based on presenting concern.…”
Section: The Empathic Counselor Response Scalementioning
confidence: 99%